PROGRAM COACHING CLINIC UNTUK MENINGKATKAN KEPERCAYAAN DIRI TERHADAP KECEMASAN BERBICARA SANTRI MTA DARUL FALAH SELANGOR - Danifatussunah, Azkiyatun; Nabhan, Ghifari; Wijayanti, Erna (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Public speaking skills still need to be wholly owned by students. This reluctance to appear publicly is due to low self-confidence and minimal mastery of public speaking techniques. This inability causes communication that should be effective to be degraded. There often needs to be more clarity in communication in public. These misconceptions are documented and spread all over the web. Santri also becomes vulnerable to acts of bullying or bullying in cyberspace. This Community Service activity by the UIN Walisongo International KKN team, held at Ma'had Tahfiz Darul Falah Selangor, aims to assist students at the ma'had. Hence, they have good public speaking skills using the coaching clinic method. The results of this activity indicated that students who initially had low public speaking skills experienced an increase in their public speaking skills following the mentoring activities for learning to speak in public. This is indicated by students' positive responses while participating in the action, and the questionnaire results related to students' perceptions of the activity.